Clinical and Radiological Findings of Autosomal Dominant Osteopetrosis Type II: A Case Report - Priyanka Kant; Neelkamal Sharda; Rahul R. Bhowate (Hindawi Limited, 2013)
Osteopetrosis is a rare inherited genetic disease characterized by sclerosis of the skeleton caused by the absence or malfunction of osteoclasts. Three distinct forms of the disease have been recognized, autosomal dominant osteopetrosis being the most common. Autosomal dominant osteopetrosis exhibits a heterogeneous trait with milder symptoms, often at later childhood or adulthood. The aim of this case report is to present the clinical and radiographic features of a 35-year-old female patient with autosomal dominant osteopetrosis type II who exhibited features of chronic generalised periodontitis, and the radiographs revealed generalised osteosclerosis and hallmark radiographic features of ADO type II, that is, "bone-within-bone appearance" and "Erlenmeyer-flask deformity."